2013
DOI: 10.1017/s104161021200227x
|View full text |Cite
|
Sign up to set email alerts
|

Care workers’ abusive behavior to residents in care homes: a qualitative study of types of abuse, barriers, and facilitators to good care and development of an instrument for reporting of abuse anonymously

Abstract: Lack of resources, especially care worker time and knowledge about managing challenging behavior and dementia were judged to underlie much of the abuse described. We describe the first instrument designed to measure abuse by care home workers anonymously; field-testing is the logical next step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 12 publications
3
51
0
1
Order By: Relevance
“…35,36 Several factors are involved in the presence of abuse in older people such as socioeconomic, sociodemographic and psychological ones, quality of life, and the presence of comorbidities. [37][38][39][40] Some of these factors are also described in our study as being associated with abuse. Thus, the presence of malnutrition, neurocognitive disorders, depression, and anxiety syndrome are associated with the presence of abuse.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…35,36 Several factors are involved in the presence of abuse in older people such as socioeconomic, sociodemographic and psychological ones, quality of life, and the presence of comorbidities. [37][38][39][40] Some of these factors are also described in our study as being associated with abuse. Thus, the presence of malnutrition, neurocognitive disorders, depression, and anxiety syndrome are associated with the presence of abuse.…”
Section: Discussionsupporting
confidence: 64%
“…Several factors are involved in the presence of abuse in older people such as socioeconomic, sociodemographic and psychological ones, quality of life, and the presence of comorbidities . Some of these factors are also described in our study as being associated with abuse.…”
Section: Discussionsupporting
confidence: 53%
“…Difficulties in estimating prevalence and incidence of institutional elder abuse is referred in various studies, 6,14,15 with underreport being the justification found for this fact. 1,2,16 Possible explanations for underreport have been proposed, such as elderly feeling of shame and fear of retaliation after disclosing the abuse to the authorities, 6,14,17,18 lack of elderly knowledge on how to do it 6 or their inability to communicate, due to mental disability or other, 6,18 this corresponding to 47.2% of our sample. Another explanation would be fear of reprisal and criminal consequences experienced by nursing homes' staff when admitting an abusive behaviour or denunciating one perpetrated by their co-workers.…”
Section: Discussionmentioning
confidence: 87%
“…Cooper et al also suggested the establishment of caregivers' education on mental illnesses, such as dementia, team work and management of challenging behaviours, as a preventive strategy at potential abuser's level. 18 Understanding why institutional abuse occurs might prove to be more important than making out its prevalence, in order to elaborate preventive strategies. 6 So, it is important to study the characteristics of the nursing homes, in a way to potentially promote modifications to the legislation and proposals on educational programs attended by institutional caregivers.…”
Section: Limitations and Suggestionsmentioning
confidence: 99%
“…While the majority of research focuses on elder abuse within the family, elder abuse in residential aged care facilities (RACFs) is an increasing area of concern . As with familial elder abuse, obtaining accurate data on the prevalence of abuse in RACFs remains an ongoing challenge . Older people regardless of setting may not recognise certain behaviours as abusive and/or may be scared or reluctant to report it.…”
Section: Introductionmentioning
confidence: 99%